2011
DOI: 10.1186/1752-4458-5-17
|View full text |Cite
|
Sign up to set email alerts
|

A mental health training program for community health workers in India: impact on knowledge and attitudes

Abstract: BackgroundUnmet needs for mental health treatment in low income countries are pervasive. If mental health is to be effectively integrated into primary health care in low income countries like India then grass-roots workers need to acquire relevant knowledge and skills to be able to recognise, refer and support people experiencing mental disorders in their own communities. This study aims to provide a mental health training intervention to community health workers in Bangalore Rural District, Karnataka, India, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 45 publications
8
109
1
Order By: Relevance
“…This is an unfortunate missed opportunity considering that a recent household survey in a major South Indian city found that over 50% of people believe in the myth that 'suicide happens without warning' (Poreddi et al, 2016). Similarly, few articles recognised the link between poor mental health and drug/alcohol abuse with suicidality, both major risk factors for suicide (Armstrong et al, 2014;Borges et al, 2017;Cavanagh et al, 2003;Cottler et al, 2005;Hawton and van Heeringen, 2009;Nock et al, 2008) and something that is a challenge to address in India where mental health literacy is low and stigmatising attitudes are prominent (Armstrong et al, 2011;Hofmann-Broussard et al, 2017;Shidhaye and Kermode, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This is an unfortunate missed opportunity considering that a recent household survey in a major South Indian city found that over 50% of people believe in the myth that 'suicide happens without warning' (Poreddi et al, 2016). Similarly, few articles recognised the link between poor mental health and drug/alcohol abuse with suicidality, both major risk factors for suicide (Armstrong et al, 2014;Borges et al, 2017;Cavanagh et al, 2003;Cottler et al, 2005;Hawton and van Heeringen, 2009;Nock et al, 2008) and something that is a challenge to address in India where mental health literacy is low and stigmatising attitudes are prominent (Armstrong et al, 2011;Hofmann-Broussard et al, 2017;Shidhaye and Kermode, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The cadres' performance has been particularly visible in the field of maternal and child health. In Indonesia, however, 90% of patients with mental disorders do not receive even basic mental health care [17]. Case-finding for them and their prognosis are often affected by the perception and attitude of society toward mental disorders, which is highly dependent on their knowledge toward mental disorders [18].…”
Section: Cadres' Perception Toward Mental Disorders and Internationalmentioning
confidence: 99%
“…Based on the results of the present study, it is needed to add the contents such as causes of mental disorders and possibility of recovery to the program. Correct knowledge about the causes of mental disorders can reduce the stigma against mental illness [17]. In contrast, whether a cadre had ever met the actual cases with mental disorders like the third vignettes were associated with the in views on mental health (Table 4).…”
Section: Cadre Experience In Training About Mental Healthmentioning
confidence: 99%
“…The implementation of this model will require involvement of key stakeholders, which will include both the public and private sectors. However, Armstrong et al [17] argue that improving the mental health literacy alone of primary healthcare staff is insufficient. There should be continued supervision and training manuals should be culture-sensitive and adaptable to local contexts.…”
Section: Mental Health At Primary Healthcare Levelmentioning
confidence: 99%
“…There should be continued supervision and training manuals should be culture-sensitive and adaptable to local contexts. [17] Nigeria opted to include mental health in primary health in 1989. However, a 2013 research article indicated that this had not been implemented.…”
Section: Mental Health At Primary Healthcare Levelmentioning
confidence: 99%